Implementasi Kebijakan Vaksinasi Covid-19 Di Kecamatan Sangatta Utara Oleh Dinas Kesehatan Kabupaten Kutai Timur - Chika Putri Aprilia; Tri Sulistyaningsih; Salahudin Salahudin (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2022)
The purpose of this study is to analyze the problems and supporting factors of the implementation of the Covid-19 vaccination policy carried out by the East Kutai District Health Office in North Sangatta District. This research is important to do in order to enrich research on the implementation of the Covid-19 vaccination policy so that it can be used as a reference and comparison for further research. The theory used in this research is the theory of policy implementation according to George Edward which states that there are four crucial variables in policy implementation. In this study using a descriptive approach with qualitative research methods. Sources of data used are secondary data and primary data taken from interviews with several respondents who are the people of North Sangatta District and also from the Health Office of East Kutai Regency, both interviews and data in other forms. The findings obtained are that people who carry out the second dose of vaccination tend to decrease for several reasons, one of which is that some people only follow the first vaccine as a condition for traveling outside the region. In general, the implementation of the Covid-19 vaccination in North Sangatta District itself has been carried out well according to the technical instructions for the Covid-19 vaccination implementation, but there are several things that still need to be improved so that the implementation of the Covid-19 vaccination in North Sangatta District is getting better. to the future.